An improved circuit-based model of a grounding electrode by considering the current rate of rise and soil ionization factors - Mokhtari, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
The behavior of a grounding system can be predicted by using either the electrical equivalent circuit models or electromagnetic computation. Despite its advantages over the latter, the equivalent circuit model fails to accurately predict the behavior under transient conditions due to the absence of two key factors, namely: 1) the current rate-of-rise and 2) soil ionization. This paper proposes a method to enhance the performance of the equivalent circuit model by taking into consideration of both mentioned factors. It is discovered that by using the proposed method, the estimated values of and of the equivalent circuit model are improved. The computed inductance dynamically changes with the change in the lightning current parameters, thus improving its accuracy for all current rate-of-rise conditions. The soil ionization effect is implemented as recommended by CIGRE, and this further improves the accuracy of the model. As a result, the voltage response of the model becomes more accurate and comparable to the electromagnetic computation results. Another important feature of the proposed model is that it can be directly applied or connected to power system equipment. Thus, an accurate grounding system effect on the transient performance of key power equipment, such as surge arresters, can be obtained.